THE EFFECT OF IMMERSION DENTURE BASE HEAT CURED ACRYLIC RESIN IN CLORHEXIDINE AND ROSELLA FLOWER EXTRACT OF CANDIDA ALBICANS: PENGARUH PERENDAMAN BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS DALAM KLORHEKSIDIN DAN EKSTRAK BUNGA ROSELLA TERHADAP JUMLAH CANDIDA ALBICANS - Zulkarnain, M.; Safitri, Eka (Dentika: Dental Journal, 2016)
Materials for the denture base are generally made of heat cured acrylic resin. A dentist is obligated to give instructions about how to use and clean the dentures. One of the natural cleaning solution that can be used is rosella flower’s extract (Hibiscuss sabdariffa). The purpose of this research is to know the influence of rosella flower’s extract against the amount of Candida albicans. The design of this study is experimental laboratoris. The sample is made of heat cured acrylic resin with sizes 10x10x1 mm, 30 pieces divided into 5 groups of treatment with each of the sample test. Each test sample soaked in klorheksidin and rosella flower’s extract concentration 30%, 40%, 50%, and aquades for 15 minutes. The amount of Candida albicans on each specimen is calculated using one-way ANOVA to see the influence of soaking and LSD to see which treatments have a significant difference between groups. Plate test and rosella flower’s extract sterilized by autoclave 121 ° C for 1 hour and then put in saliva for 1 hour so that the test plate in accordance with the state of the oral cavity and rinsed with Phosphate Buffered Saline (PBS) for 2 times. Plate test later in contamination with Candida albicans by means of a tube inserted into erlenmeyer containing a suspension of Candida albicans, then incubated for 24 hours at 37 ° C. After 24 hours, the test plates are removed from the test tube and rinsed with PBS 2 times. Test plates were divided into five groups. Test results indicate that there is a difference of LSD influence between soaking with a rosella flower’s extract concentration 30% compared to 50% p = 0.0001 (p < 0.05) and there is a difference between rosella flower’s extracts concentration of 40% compared to 50% p = 0.0001 (p < 0.05). The result of this study concluded that soaking denture base heat cured acrylic resin with rosella flower’s extract concentration 50% have the same influence on klorheksidin in inhibiting the amount of Candida albicans.